Interior design project [videorecording (DVD)] : green design - Hagen, Brandi (Learning Zone Express, 2009)
"Green design or designing with the environment in mind is not just a trend, but a personal choice to consider your impact on the earth. Join principal designer Brandi Hagen of Eminent design as she shares the components of green interior design. Discover "green" options as Brandi shows examples of environmentally friendly design options."--Container.